Challenges for Coastal Children: Investigating the Causes of School Dropout in the Southern Coastal Area of Bangladesh - Hossain, Md. Saddam; Yeasmin, Farhana; Kabir, Md. Shahjahan; Al-Mahde, Abdul Elah (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2025)
Coastal areas in Bangladesh are highly vulnerable to environmental and socioeconomic issues, leading to significant setbacks in children’s education. In a disaster-prone area like Satkhira, Shyamnagar Upazila, the root causes for high rates of student dropouts in schools are interlinked with the natural calamities of the land. This study aims at identifying the multifaceted challenges tending to school dropouts in the disaster-prone coastal area of Shyamnagar Upazila, Bangladesh. To achieve the aim, this study employs an exploratory qualitative design and purposive sampling, including structured interviews for 34 participants: 10 dropout children (aged between 10–16), 12 parents of dropout children, and 12 teachers from primary and secondary schools. Findings highlight that there are factors, such as natural calamities and scarcity of water, that directly hinder the education process and increase dropout rates. Economic constraints force children to leave schools so that they can work and earn money, alongside sociocultural factors such as child marriage and other gender norms. The study found that people who dropped out of school feel remorse and want to go back to school but get little or no assistance from the stakeholders. Inadequate infrastructure, sociocultural barriers, and psycho-social issues are also contributors to school dropouts.